Should Government be the Only Provider of Social Protection in Developing Countries? A Case of Indonesia - Nini Salwa Istiqamah (Universitas Pendidikan Ganesha, 2023)
The rapid expansion of social protection schemes is developing, not only in industrialized states but also in developing countries. This shift implies a growing recognition of social safety nets' essential role in achieving equitable and sustainable development. This trend is also crucial to support the global effort to alleviate poverty. This essay analyzes which actor should provide social protection in developing countries. It is essential to analyze the social protection discourse among scholars and international organizations and then examine which actor should be responsible for the protection. This study employs qualitative research, collecting the data through library research. This study argued that based on a moral, philosophical approach, ideally, the government should be the only provider of social protection. However, in developing countries, resources are limited, meaning external parties should also be encouraged to contribute to social protection schemes. This statement is proven in the case of the Indonesian government's experience in providing social protection for its people.